Comparative evaluation of Knoop hardness and depth of cure of ORMOCER based resin composites - Alonso, Roberta Caroline B.; Cunha, Leonardo G.; Correr, Gisele M.; dos Santos, Paulo H.; Sinhoreti, Mário Alexandre C. (Brazilian Dental Science, 2010)
The purpose of this study was to evaluate the Knoop hardness and the depth of cure of Ormocer based composites and to compare them with traditional Bis-GMA or derivatives based composites. Four composite were selected: Two Ormocer based (Definite and Admira), a hybrid (Z250) and a microfilled (A110). Cylindrical specimens with 3mm in diameter for 5mm in height were prepared in a metallic mould and photoactived according the manufacturer’s instructions with the curing light unit XL2500 (3M/ESPE). After, they were stored for 24 hours at 37ºC. Knoop hardness measures were obtained with Micro hardness tester HMV (Shimadzu-Japan), with a load of 50g for 15s. Five specimens were made for each resin composite and three Knoop hardness measurements were obtained on surface, 1mm, 2mm, 3mm and 4mm depths. The results were submitted to ANOVA and Tukey’s test at 5% level. According to the results, at all depths, Z250 was harder than the others composites. The composites Definite, Admira and A110 had no statistical differences in KHN until the depth of 2mm, after A110 showed decrease in hardness values. Generally, for all tested materials the deeper layers showed lower Knoop hardness values than those of the surface. Compared with hardness surface, statistically significant reductions in KHN occurred at depths of 2mm for Z250 and A110 and 3mm for Definite and Admira. It could be concluded that ORMOCER based materials showed intermediated hardness values and satisfactory depth of cure, when compared to the conventional composites.